Effects of training on cattle grazing spotted knapweed and Canada thistle - Tierney, Katie Rene' (Montana State University - Bozeman, College of Agriculture, 2013)
Spotted knapweed (Centaurea stoebe L.) and Canada thistle (Cirsium arvense (L.) Scop.) are changing and degrading North American rangeland ecosystems by replacing native grasses and forbs. Conventional control methods are often not cost-effective. Using livestock to manage invasive species offers a potentially cost effective alternative. The objectives of our first study were to determine if: 1) cattle trained to consume spotted knapweed and Canada thistle in 2004 retained their training in 2011, 2) calves and yearlings of the 2004 trained cattle consume more spotted knapweed and Canada thistle than calves and yearlings from untrained cows, and 3) yearlings trained to graze Canada thistle in mid-July consume more of the weed than untrained yearlings in late July and late August. In our 2011 study, trained cattle did not spend more time grazing spotted knapweed or Canada thistle than untrained cattle. In 2011, calves and yearlings from trained cattle did not spend more time grazing spotted knapweed or Canada thistle than those from untrained cattle. Yearlings trained to graze Canada thistle consumed similar amounts as untrained yearlings when grazed in July and less than untrained yearlings in August. The objectives of our second study were to determine if: 1) individual cattle spent similar amounts of time grazing spotted knapweed in 2011 and 2012, and 2) individual yearlings affect time spent grazing spotted knapweed of their peers. Individual animals tended to spend similar amounts of time grazing spotted knapweed in July of 2011 and 2012. Grazing yearlings, that tended to spend high or low amounts of time grazing spotted knapweed, together did not affect their time spent grazing this weed. Cattle innately grazed spotted knapweed (20-50% of their time grazing) and, to a much lesser extent, Canada thistle (0-17% of their time grazing); training did not result in greater amounts of time spent grazing these weeds. Individual cattle with the innate behavior to graze spotted knapweed can be identified and retained in herds to potentially increase grazing of spotted knapweed. With proper grazing management, cattle grazing can be used as one tool in an integrative approach to control spotted knapweed on rangelands.
Keywords: Range management; Spotted knapweed; Canada thistle; Weeds--Control; Rangelands; Ecology; Cattle